Promoção de crescimento de cultivares de alface pela levedura rizosférica Torulaspora globosa - Cabrini, Paloma Garcia (Universidade Federal de São Carlos, 2018)
The soil harbors great microbial diversity which remains unknown, as regards species, microbial groups and functions in the ecosystem. Among the known microorganisms that inhabit the soil, one group is described as beneficial to agricultural activities: the plant growth promoter microorganisms (PGPM). They are able to aid the development of plants through, mainly, the production of phyto-hormones, nutrients solubilization and control of phytopathogens. Among the PGPM, yeasts present slight prominence, because they are in less quantity in the soil. However, studies in the literature indicate that this group presents great potential, as it presents excellent results in in vitro experiments, regarding the main mechanisms of stimulus to plant development. Considering the above, the objective of this work was to evaluate the germination, initial development of seedlings, seedlings and adult lettuce plants inoculated with the rhizosphere yeast Torulaspora globosa and its metabolites. Two experiments were realized; the first consisted of the inoculation of seeds and lettuce seedlings of the Crocantela variety under greenhouse conditions, germinated in substrate and transplanted to the field. The second experiment consisted of evaluating, under laboratory controlled conditions, the action of yeast, its metabolites and tryptophan on germination and initial development of lettuce (Crocantela and Valentina varieties). Finally, the action of the diazotrophic bacterium Azospirillum brasilense, alone and co-inoculated with the yeast, was evaluated in the development of the Valentina variety. The results showed that for yeast and field trials, yeast inoculation provided seedlings with a lower root length, despite a higher root mass (smaller and more branched root system). The leaves appeared wider and longer, which was reflected in a larger mass of the aerial part. The evaluation of the plants at the post-harvest showed that for the variables height, leaf number, leaf length and width, and fresh weight of shoot, the noninoculated treatment had statistically lower values. The results for the trials under controlled conditions showed that the treatment of the seeds of the cultivars Crocante and Valentina did not affect significantly the germination. The seedlings, however, of the Crocantela variety showed roots smaller and with less area when treated with the yeast and its metabolites. The metabolites of the yeast with tryptophan (T7), in turn, provided a larger root diameter. The data obtained by the Valentina variety showed that the treatment with yeast, its metabolites and addition of tryptophan (T5) provided the best results, especially for volume, root area and number of root tips. The treatments with tryptophan addition (with yeast (T6) or metabolites (T7)) presented the least satisfactory results for the development of the seedlings. It was possible to observe that the treatment 5 also showed the best in stimulating the production of root hair for the Valentina variety. The addition of the A. brasilense, isolated and in co-inoculation with the yeast, did not promote significant growth of lettuce seedlings of the Valentina variety. From the data presented we can observe that the inoculation of the seeds and seedlings with the yeast showed to be efficient in the promotion of lettuce growth. Studies related to inoculation methods, inoculum formulations, cell concentrations and chemical analysis of the metabolites produced, however, are imperative to optimize the results of growth promotion and the establishment of the technology.
Growth promotion of lettuce varieties by rhizosphere yeast Torulaspora globosa
Keywords: Micro-organismos promotores de crescimento vegetal; Crocantela; Valentina; Olerícolas; Metabólitos microbianos; Plant growth promoter microorganisms; Horticulture; Microbial metabolites; CIENCIAS BIOLOGICAS::MICROBIOLOGIA